GELORA KEELOKAN JIWA PEREMPUAN PADA IKLAN WARDAH - Amalia, Dina; Sudarsono, Achmad Budiman; Nurhayati, Kristina; Marta, Rustono Farady; Engliana (Kinesik, 2024)
Beauty product advertisements in general are always identified with displays that show the beauty of the ideal physical form of women, such as tall stature, fair-skinned, slim figure, and beautiful, flawless facial complexion. In contrast to the advertisements circulating in general, Wardah depicts beauty through the body image of five female figures and one of them features a disabled woman wearing a prosthetic leg as a medium for conveying messages in advertising. Wardah aims to challenge the conventional notion of beauty, which predominantly focuses on physical appearance, by featuring a disabled individual as the main protagonist in their campaign. This paper seeks to analyze the portrayal of the female physiques depicted in Wardah beauty advertising through the application of the semiotic analysis approach based on the John Fiske model, in conjunction with the idea of constructing social reality. This research will be based on the constructivism paradigm to identify the three primary tiers of Fiske's semiotic analysis, including: level of reality, level of representation, and level of ideology.